Biosorptive Potential of Pseudomonas species RY12 Toward Zinc Heavy Metal in Agriculture Soil Irrigated with Contaminated Waste Water. Issue 3 (27th August 2022) - Yasmin, Riffat; Zafar, Muhammad Shoaib; Tahir, Imtiaz Mahmood; Asif, Rizwan; Asghar, Samra; Raza, Syed Kashif
Industrial waste is mainly responsible for accumulating Zn (II) in the soil, which needs to be removed to avoid its bioaccumulation and hazardous effects on the environment. In a recent study, the potential of the RY12 strain was evaluated as a biosorbent of Zn (II) ions in an aqueous medium. Different microbiological techniques like biochemical, molecular characterization, and 16S rRNA gene sequencing were used for the identification of RY12. The impact of different parameters such as the initial zinc ion concentration, pH, temperature, and the removal of other metals such as manganese, lead, cobalt, silver, copper, mercury, and chromium was also evaluated on the reduction of Zn (II). Fourier Transform Infrared spectroscopy (FTIR) was also carried out to investigate the role of cellular surfaces in the sorption of Zn+2 ions. Both biochemical and phylogenetic analyses established that strain RY12 Pseudomonas sp. capable of reducing Zn +2 up to 89% at 28°C (pH = 6.5; initial Zn +2 concentration = 200 mg/L). The FTIR analysis revealed that the bacterial cell wall's amino, carboxyl, and phosphate groups were involved in the reaction with Zn (II). Our findings suggest that Pseudomonas sp. RY12 is a proficient bacterium for removing zinc from industrial waste and could be a valuable bioremediation agent.